Fa’ālīyatu al-Mawād at-Tafā’uliyyah @Liveworksheet fī Taḥsīni Natāiji Ta’allumi al-Lugah al-‘Arabiyyah ladā Ṭullābi Ma’had Wādī al-‘Ulūm al-Islāmy Bāṭy: Effectiveness of Interactive Learning Material @Liveworksheet in increasing the grading score of students at the Islamic Boarding School - Fadhilah, Isna; Subhan, Ali; Raodah (Universitas Negeri Semarang, 2025)
Arabic Learning at Islamic Boarding School still faces a complex problem, such as limitation of media, low utilization of technology, and lack of motivation and active participation of students. At Wadil Ulum Islamic Boarding School, students tend to memorize vocabularies reluctantly and fail to optimize technology in learning. This research aims to explain the process of learning arabic by using Interactive @Liveworksheet Modul and measure its level of effectiveness. This research used quantitative approach with one group pretest-posttest design. Data collecting technique used instrument of test, observation, and documentation. Shaphiro Wilk in normality test, Levene test in homogenity test and Paired sample T-test in hypothesis test were used in data analysis technique. The research finding showed that Interactive @liveworksheet modul was effective to use to improve the students’ arabic learning outcome at Wadil Ulum Islamic Boarding School. The result finding was evidenced by an average score of 48.3 on the pre-test, and 85.8 on the post-test. Thus, there was 37,5% of improvement between pre-test and post-test. Meanwhile, the result of hyphothesis test showed that accepted significance value was 0,000, in which significance score 0,00 < 0,05. Therefore, Ha was accepted and H0 was rejected. This finding concludes that the interactive module @Liveworksheet is effective in improving Arabic learning outcomes.